Differential mesolimbic and prefrontal alterations during reward anticipation and consummation in positive and negative schizotypy. (30th August 2016) - Yan, Chao; Wang, Yi; Su, Li; Xu, Ting; Yin, Da-zhi; Fan, Ming-xia; Deng, Ci-ping; Wang, Zhao-xin; Lui, Simon S.Y.; Cheung, Eric F.C.; Chan, Raymond C.K.
Abstract: Schizotypy is associated with anhedonia. However, previous findings on the neural substrates of anhedonia in schizotypy are mixed. In the present study, we measured the neural substrates associated with reward anticipation and consummation in positive and negative schizotypy using functional MRI. The Monetary Incentive Delay task was administered to 33 individuals with schizotypy (18 positive schizotypy (PS), 15 negative schizotypy (NS)) and 22 healthy controls. Comparison between schizotypy individuals and controls were performed using two-sample T tests for contrast images involving gain versus non-gain anticipation condition and gain versus non-gain consummation condition. Multiple comparisons were corrected using Monte Carlo Simulation correction of p <.05. The results showed no significant difference in brain activity between controls and schizotypy individuals as a whole during gain anticipation or consummation. However, during the consummatory phase, NS individuals rather than PS individuals showed diminished left amygdala and left putamen activity compared with controls. We observed significantly weaker activation at the left ventral striatum during gain anticipation in NS individuals compared with controls. PS individuals, however, exhibited enhanced right ventral lateral prefrontal activity. These findings suggest that different dimensions of schizotypy may be underlied by different neural dysfunctions in reward anticipation and consummation. Highlights: We examined the neural correlates of reward anticipation and consummation in schizotypy. Negative schizotypy showed reduced left amygdala and putamen responses to consummation of reward. Negative schizotypy showed reduced ventral striatal response to anticipation of reward. Positive schizotypy showed enhanced ventral lateral prefrontal response in reward anticipation.